The Impact of Educational Intervention Programs to Promoting Mammography Screening: A Systematic Review - Seyed Mohammad Mehdi Hazavehei; Khadije Ezzati-Rastegar; Mitra Dogonchi; Nooshin Salimi; Elham Gheisvandi (Journal of Education and Community Health)
Background and Objectives: Breast cancer accounts for almost 30% of all cancers and is the second leading cause of cancer deaths in women. The World Health Organization introduces two main measures to prevent breast cancer including relevant education and mammography as the fastest way of diagnosis before the appearance of disease symptoms.This study aimed systematic review to evaluate educational interventions designed to increase the rate of mammography screening. Materials and Methods: We searched electronic databases published between January 2010 to February 2016 and inclusion criteria through Embase, Google Scholar, Scopus, Cochrane, PubMed, Web of Science, SID, Iran Medex, and Iran Doc, selected the articles that focused on determining educational interventions. Results: Most of the studies were RCT. Interventions were more educational, motivational and supportive and were performed in different times. Data collection was in self-report method and an expected impact was action to mammography screening. Conclusions: Identification of effective factors in mammography and using the appropriate interventions as well as effective strategies in the knowledge, attitude and behavior fields will lead to early detection and treatment of breast cancer.